Uji Ekstrak Kulit Buah Mangga Arum Manis dalam Etanol pada Tumbuh Kembang Escherichia coli dan Salmonella typhi - Mandike Ginting; Suprianto; Siti Fatimah Hanum; Debi Meilani; Maya Sartika (Jurnal Indah Sains dan Klinis, 2022)
Antibacterial interferes with growth and development and even kills by interfering with microbial metabolism. The peel of Mangifera indica L.var. arum manis contains antibacterial flavonoids. Research for the detection of antibacterial activity of mango peel extract of arum manis varieties in ethanol on E. coli and S. typhi. The well diffusion method was used with concentrations of 20.0%, 30.0% and 40.0%; chloramphenicol as a positive control. The diameter of the inhibition zone as an indicator of E. coli activity was 12.83 mm; 12.93 mm; and 13.91 mm, against S. typhi 11.60 mm; 12.52 mm; and 13.40 mm at these concentrations, respectively. Ethanol extract of Mangifera indica L. var. arum manis has antibacterial activity of E. coli and S. typhi with strong inhibitory power, and without differences in concentration